Parametric Optimization of Pulsed Nd:YAG Laser Lap Welding of Stainless Steel ASTM A240/ 316L with Carbon Steel ASTM A570/Gr30 - Tawfiq, Thaier A. (Al-Nahrain Journal for Engineering Sciences, 2017)
This work describes seam welding process using dissimilar ferrous metals by pulsed Nd:YAG. The main objective of this work is to achieve the best welding conditions. This imposes careful selection for the welding parameters and inevitably the well design of experiment (DOE). Sheets of ASTM A240/316L stainless steel to ASTM A570/Gr30 carbon steel all of 0.5 mm in thickness were lap welded. Different pulse energies or the related peak power, pulse duration, pulse repetition rate, and welding speeds were used. Moreover, different welding speeds were controlled by the employed manipulator. The laser beam spot diameter and the standoff distance were fixed. Experimental results are supported by the computational 2D and 3D models. In this article response surface methodology (RSM) was applied to design the experiment and obtain the best parameters through a set of mathematical models that define the weld characteristics. The results show that the best joint in term of joint strength is obtained at 31.9 J pulse energy (related to 5.5 kW peak power and 5.8 ms pulse duration), power density of 1.43×106 W/cm2, 1.5 Hz pulse repetition rate, and 0.5 mm/s welding speed.